QUO VADIS TRANSISI DEMOKRASI : Arah Demokratisasi Indonesia ditengah Demokrasi Pasar - Ali Martin . (SPEKTRUM, 2010)
Abstract This article examines the process of democratic transition that took place in several countries, especially Indonesia. Where is the democratic transition is the collapse of authoritarian regimes, the situation toward a democratic regime. But in reality it is not got to the transition towards a democratic regime, but can return to an authoritarian regime where there is a failure in the process of consolidating civilian, even a democratic transition happens now is controlled by the democratic form of market neo-liberalism. Indonesia is no exception to the democratic transition by adherence to a market democracy. Keywords: transition to democracy, authoritarian, democratic market